Occurrence and Drivers of Antibiotic Resistance Genes Carried by Bacteriophages in Soils Following Different Fertilization Treatments - Zhang, Mingdi; Guo, Yajie; Zhang, Yue; Hu, Xueying; Cheng, Shoutao; Wang, Xuming (Toxics (Basel), 2025)
Fertilization has an important effect on soil antibiotic resistance. Most recent studies have focused on antibiotic resistance genes (ARGs) harbored by bacteria (bARGs); however, little is known about ARGs carried by soil bacteriophages (pARGs) under different fertilization treatments. Here, 24 pARG subtypes were quantified in soils with long-term application of different fertilizers using droplet digital PCR (ddPCR). The results showed that the detection rates of the target ARGs in bacteriophages were 66.67%, 70.83%, and 75.00% in unfertilized, chemically fertilized, and organically fertilized soils, respectively. The total abundance of pARGs in soils amended with organic fertilizer was significantly higher than that in unfertilized and chemically fertilized soils. The multidrug resistance gene (mexF) exhibited the highest abundance in soils amended with organic fertilizer. A significant positive correlation was observed between bARGs and pARGs, and the detected pARG subtype abundances were one to two orders of magnitude lower than those of the corresponding bARGs. The results of variation partitioning analysis revealed that the interaction between the bacterial community and soil properties drove the variation in soil pARGs. Our findings indicate that bacteriophages are important vectors of ARGs, in addition to bacteria, in agricultural soils, and their contribution to antibiotic resistance should not be overlooked.